PENGARUH MODEL PjBL BERBASIS LITERASI ILMIAH TERHADAP PENINGKATAN HASIL BELAJAR IPAS KELAS V SD - Cahyani, Widya Putri; Nuvitalia, Duwi; Mardliyah, Siti; Ulumuddin, Arisul (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research aims to determine the influence of the scientific literacy-based Project Based Learning (PjBL) model on science learning outcomes for VC class students at SDN Jatingaleh 01. This research uses a quantitative experimental approach using a one-group pretest-posttest design research design. This research involved 25 VC class students and used saturated sampling for sample selection. With a sample size of 25 respondents which is the same as the population size. The research will collect data using tests, observations, interviews and documentation. The T-test is a data analysis technique used in this research. This research found that the Scientific Literacy-based Project Based Learning (PjBL) model had a significant positive impact on the learning outcomes of VC class students at SDN Jatingaleh 01 in the science and sciences subject My My Pride. The paired sample T-test shows a t value of -9.072 with a significance value of 0.000. This shows its significance value. The p value (2-tailed) is 0.00 smaller than the significance level of 0.05.